Hyperuricemia and its Association with the Presence of Metabolic Syndrome among Indonesian Obese Adolescents - Pramono, Adriyan; Nuryanto; Murbawani, Etisa Adi; Panunggal, Binar; Anjani, Gemala (Pakistan Journal of Nutrition, 2016)
Metabolic syndrome (MetS) plays an important role in inflammation and insulin resistance. Increasing number of adolescents MetS were common among obese. The inflammatory biomarkers may contribute to increasing levels of uric acid (UA). Currently UA is not only associated with gout, but also cardiovascular disease. This was a cross sectional study conducted in Semarang City, Indonesia. Consecutive sampling for obese adolescents was administrated. About 81 obese adolescents from two government highs schools were recruited in this study. We measured anthropometry (weight, height, waist circumference, neck circumference), clinical data (systolic and diastolic blood pressure) and biochemical data (triglyceride, HDL-cholesterol, fasting blood glucose, uric acid). A subjects was categorized as MetS if presence 3 or more components of MetS. Gender and Hyperuricemia was associated with presence of MetS (p = 0.048 and p = 0.004). The mean levels of UA increased accordance to the amount of MetS components (p = 0.000). Regression logistic analysis concluded that hyperuricemia as major risk factor of MetS among obese adolescents (OR = 3.97). Hyperuricemia contributed to metabolic syndrome among Indonesian obese adolescents.